2016
DOI: 10.1212/wnl.0000000000003373
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular reactivity and white matter integrity

Abstract: Objective: To compare the diffusion and perfusion MRI metrics of normal-appearing white matter (NAWM) with and without impaired cerebrovascular reactivity (CVR).Methods: Seventy-five participants with moderate to severe leukoaraiosis underwent blood oxygen level-dependent CVR mapping using a 3T MRI system with precise carbon dioxide stimulus manipulation. Several MRI metrics were statistically compared between areas of NAWM with positive and negative CVR using one-way analysis of variance with Bonferroni corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 42 publications
4
41
0
Order By: Relevance
“…), microstructural damage of the cerebral white matter (Sam et al . ), and increased mortality (Portegies et al . ).…”
Section: Age and Cvmrmentioning
confidence: 99%
See 1 more Smart Citation
“…), microstructural damage of the cerebral white matter (Sam et al . ), and increased mortality (Portegies et al . ).…”
Section: Age and Cvmrmentioning
confidence: 99%
“…Mechanistically, carotid arterial stenosis or occlusion may decrease CPP distal to the lesions and exhaust the autoregulatory vasodilatory reserve; therefore, additional stimuli such as hypercapnia may not further vasodilate the cerebral arteries (Gupta et al 2012). In addition to stroke, attenuated hypercapnic CVMR has been shown to correlate with cognitive decline in AD patients (Silvestrini et al 2006), microstructural damage of the cerebral white matter (Sam et al 2016), and increased mortality (Portegies et al 2014).…”
Section: Age and Cvmrmentioning
confidence: 99%
“…Prior studies showed impaired white matter CVR is associated with disruption of white matter at the microstructural scale in participants with WMH (Sam, Conklin, Holmes, et al, 2016;Sam, Peltenburg, Conklin, et al, 2016). Prior studies showed impaired white matter CVR is associated with disruption of white matter at the microstructural scale in participants with WMH (Sam, Conklin, Holmes, et al, 2016;Sam, Peltenburg, Conklin, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Impaired cerebrovascular autoregulation may also be contributing to chronic ischemia (Mikulis, 2013). Exhaustion of cerebrovascular reserve and the associated chronic ischemic injury to gray matter and white matter is hypothesized as the cause of disruption of both the network nodes and edges of the connectome respectively (Sam, Conklin, Holmes, et al, 2016;Sam, Peltenburg, Conklin, et al, 2016). Exhaustion of cerebrovascular reserve and the associated chronic ischemic injury to gray matter and white matter is hypothesized as the cause of disruption of both the network nodes and edges of the connectome respectively (Sam, Conklin, Holmes, et al, 2016;Sam, Peltenburg, Conklin, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation